Urate Crystals; Beyond Joints - Ahmad, Muhammad Israr; Masood, Salman; Furlanetto, Daniel Moreira; Nicolaou, Savvas (Frontiers in Medicine, 2021)
Gout is the most common inflammatory arthropathy caused by the deposition of monosodium urate (MSU) crystals. The burden of gout is substantial with increasing prevalence of gout globally. The prevalence of Gout in the United States has increased by over 7% in the last two decades. Initially, it was believed that MSU crystal deposits occur only in the joints with the involvement of the periarticular soft tissues, but recent studies have shown the presence of MSU crystal deposition in extra-articular sites as well. Human plasma becomes supersaturated with uric acid at 6.8 mg / dl, a state called hyperuricemia. Beyond this level, uric acid crystals precipitate out of the plasma and deposit in soft tissues, joints, kidneys, etc. If left untreated, hyperuricemia leads to chronic gout characterized by the deposition of tophi in soft tissues such as the joints, tendons and bursae. With the advent of newer imaging techniques such as DECT, MSU crystals can be visualized in various extra-articular sites. Extra-articular deposition of MSU crystals is believed to be the causative factor for the development of multiple comorbidities in gout patients. Here, we review the literature on extra-articular deposition of urate crystals and the role of dual-energy computed tomography (DECT) in elucidating multi-organ involvement. DECT has emerged as an invaluable alternative for accurate and efficient MSU crystal deposition detection. Future studies using DECT can help determine the clinical consequences of extra-articular deposition of MSU in gout patients.